Patterns of olanzapine prescribing for those receiving highly emetogenic chemotherapy. Issue 28 (1st October 2022) - Childs, Daniel S; Helfinstine, David A; Sangaralingham, Lindsey R.; Orme, Jacob; O'Sullivan, Ciara Catherine; Loprinzi, Charles L.; Ruddy, Kathryn Jean
Abstract : 232 Background: Olanzapine has an important role in preventing and treating nausea and vomiting from highly emetogenic chemotherapy (HEC). This drug, for the last 5 years, has been a component of most major antiemesis guidelines. The aim of the current study was to assess how often olanzapine has been prescribed for patients receiving HEC. Methods: A retrospective analysis was performed using an OptumLabs de-identified clinical database of medical and pharmacy claims. The database was filtered for patients starting HEC in the interval of 2006 to Q2 of 2021. Descriptive statistics were used to analyze patient characteristics and year-by-year antiemetic prescribing patterns, coinciding with cycles 1 and 2 of chemotherapy. Results: A total of 63, 154 distinct patients were included. The median age was 58 years (range, 18-88). Over a quarter of the patients identified as Black, Hispanic, Asian, or other. Breast (45.2%) and hematologic (20.8%) cancers were the most common diagnoses. In 2016, olanzapine was prescribed to only 1.4% of patients with cycle 1 of HEC. Prescriptions increased modestly each year, and by 2021, 13.9% of patients received olanzapine with their first cycle of chemotherapy. An additional 5.7% of patients received olanzapine for breakthrough symptoms or enhanced prophylaxis during cycle 2. In 2021, over three-quarters of patients were prescribed antiemetics in a guideline concordant manner, with either an olanzapine-containing quadruplet (12.2%), an NK1 receptor antagonist triplet (64.5%), or an olanzapine triplet (exact number suppressed due to small sample size). Conclusions: The rate of olanzapine prescribing is less than might be expected following its inclusion in major antiemesis guidelines. This finding highlights the challenges of disseminating information and keeping prescribing systems updated with the newest evidence in supportive oncology.